Reflective Writing in Basic Nursing Concept Course: A Qualitative Study of Nursing Students - Evelyn Hemme Tambunan; Idauli Simbolon (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
Nursing students need to be trained in reflective competence as early as possible since it is an essential attribute for developing autonomous, critical and advanced practitioners in the future. However, there remains less attention in the usage at the bachelor nursing programs, particularly in the first year level. This study aimed to  explore freshman nursing students’ reflective writing experience in basic nursing concept courses. Descriptive qualitative study was used in this study. Focus group interviews using zoom meeting platform were conducted with ten participants recruited through purposive sampling using the inclusion criteria, such as freshman nursing students who successively take basic nursing concept courses in semester 1 and 2 in academic year of 2019-2020 and attended learning process using reflective writing. Data were analyzed using qualitative content analysis. The experience of freshmen nursing students of reflective writing can be summarized into three themes, including difficulty at the initial process, challenging in the progress, and satisfying at the end of the process. Although freshmen nursing students struggled to understand the purpose and work on reflective writing, by the end of the two semesters, it had become a fun and satisfying experience. It has benefited both the learning process and the students personal lives. Students will be challenged to become proficient in reflective writing and improve self regulated learning over the course of two semesters. Reflective writing utilization based on other guidelines could be adopted. Nursing student critical thinking evaluation in reflective writing successively is needed to be considered